Penerapan Standar ISO 55000 Untuk Manajemen Aset Dengan Pendekatan Metode Topsis - Salamun Salamun; Johan Saka Wikarta; Ira Puspitasari (Jurnal Komputer Terapan, 2022)
Assets are part of the facilities of a company or institution. Educational institutions, by applying the topsis method, are intended to be able to systematically choose the best alternative from several existing alternatives to be used as a problem-solving method. Abdurrab University has implemented asset management in managing assets at the university but still has not implemented the ISO 55000 standard in its management, where the use of assets is still not in line with the objectives of Abdurrab University. Besides, the asset lifecycle has not been implemented, many assets do not have a long service life. The purpose of this study is to improve asset management at Abdurrab University by implementing an ISO 55000 standard decision support system. The Abdurrab University asset management decision support system is built to the ISO 55000 standard with the topsis method and uses PHP and JavaScript programming languages and MySQL as data storage. The results of this study prove that the asset management system can be implemented to manage assets at Abdurrab University and that this decision support system can be used for asset procurement.